PENGARUH ALIH FUNGSI LAHAN HUTAN MENJADI PERKEBUNAN KELAPA SAWIT TERHADAPSIFAT KIMIA TANAH - Oksana Oksana; Mokhamad Irfan; Uiyal Huda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
This study was conducted from July to December 2011 in the Tanjung Pauh village, Sub district of Singingi Hilir, District Kuantan Singingi. The purpose of this research was to observe the impact of the conversion of forest land into oil palm plantation at various planting year on soil chemical properties, including; C-organic, N total, pH, and cat ion exchange capacity. The method used is the method Observe with correlation and regression to determine the effect of conversion of forest land into oil palm plantations. Sampling of land consists of forest, plant oil palm plantation ages various planting year 2, 8, and 16 years. The parameters analyzed were pH, C-organic, cat ion exchange capacity, nitrogen total. Results showed that conversion of forest land into oil palm plantations shows the changes in soil chemical properties including, pH, C-organic, cat ion exchange capacity, total N and organic matter. Over the conversion of forest soil led to increased soil pH, which is forest land (4.49), oil palm age of 2 years (4.52), oil palm age of 8 years (4.76) and age 16 years (5.02). The results of this study indicate oil palm plantations to oil palm trees aged 16 years, still not able to match the conversion of forests in maintaining c-organic. On forest land have C-organic content of 1.87%, and at the age of 2 years of planting 1.05%, the lowest C-organic contained in the oil palm plantation age of 8 years (1.05%), and increased at the age of 16 years (1:42%). Cat ion exchange capacity in forest land 12.72%, changed to 12.76% at the age of 2 years of planting, growing 13.15% at the age of 8 years and 9.61% at the age of 16 years of planting. Nitrogen total content of the forest land is changed to 0.0285% 0.0427 at the age of 2 years of planting, cropping 0.0425 at the age of 8 years and 0.0283 at the age of 16 years of planting.